Slaves on the Way to Recognition. Józef Tischner's Struggling with Historiosophy - Piotr Kostyło (Nicolaus Copernicus University in Toruń, 2018)
In the eighties and nineties of the twentieth century Józef Tischner was a witness and participant of the political breakthrough in Poland. The breakthrough resulted in the fall of the communist regime and in regaining freedom by the society. Describing that process, Tischner regularly was referring to Georg W. F. Hegel's philosophy, and particularly to Hegel's analyses of the master and slave relationship. Before the breakthrough, in the Polish society communist leaders were masters, whereas workers were treated like slaves. In the article the author considers three ways of achieving recognition, that is freedom by slaves. Those ways had emerged from the Hegelian tradition and became reference points for Tischner. They were: liberation through revolution, liberation through work, and liberation through solidarity. Each way entailed serious historiosophical problems which Tischner had to face. The author analyses Tischner's struggling with the philosophy of history and indicates to its possible pedagogical references.